Development of the instructional model by integrating information literacy in the class learning and teaching processes / Therdsak Maitaouthong, Kulthida Tuamsuk and Yupin Techamanee - Maitaouthong, Therdsak; Tuamsuk, Kulthida; Techamanee, Yupin (2011)
This study was aimed at developing an instructional model by integrating information literacy in the instructional process of general education courses at an undergraduate level. The research query, ―What is the teaching methodology that integrates information literacy in instructional process of general education courses at an undergraduate level?‖ was set with an aim to develop the teaching methodology that integrates information literacy in instruction of general education courses of undergraduate curricula. The research method was based on the quasi-experimental design and the nonrandomized control group pretest-posttest design. The two general education courses under study included SWU 142 Sciences for the Development of Quality of Life and the Environment and SWU 151 General Studies for Human Development. The research was divided into 4 stages: (1) The teaching plan involving the outcomes of information literacy acquisition in the general education courses was analyzed and written so that it integrated information literacy. (2) The knowledge and competency related to student information literacy were measured before and after the experiment using an information literacy proficiency test. (3) The teaching was conducted according to the teaching plan. (4) The case study reports by the students where information literacy skills were applied were evaluated by the teacher. The findings indicate that instruction which integrated information literacy of the two general education courses comprised 8 components: the learning outcomes, teaching method, learning activities, teachers‘ roles, librarians‘ roles, students‘ roles, teaching media, and learning assessment and evaluation. The instruction that integrated information literacy involved seven steps: assignment of case studies, selection of case study topics, retrieval of related information, stipulation of teaching topics, self-access learning, research presentation, and evaluation of the case studies. The experiment on the developed teaching approach in the courses SWU 142 and SWU 151 indicated that the experimental groups of both courses showed a higher level of information literacy and higher scores of group assignments after the experiment.